Effect of swift heavy ion irradiation and annealing on the microstructure and migration behaviour of implanted Sr and Ag in SiC - Malherbe, Johan B. (University of Pretoria, 2020)
Thesis (PhD (Physics))--University of Pretoria, 2019.